2008
DOI: 10.1093/rpd/ncn035
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose survey in a paediatric cardiac catheterisation laboratory equipped with flat-panel detectors

Abstract: Flat-panel X-ray detectors for fluoroscopy represent a modern imaging equipment that is being implemented in paediatric cardiac catheterisation laboratories. Infants and children represent a group of patients with a high radiosensitivity. A survey of 273 (126 diagnostic and 147 therapeutic) paediatric catheterisations was performed to investigate the radiation doses delivered by the new X-ray system. Statistical parameters (75th, 50th and 25th percentiles) of dose-area product (DAP) and fluoroscopy time are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 12 publications
(13 reference statements)
2
21
1
1
Order By: Relevance
“…The doses from the 1994 to 2000 era at Hospital 1 were compatible with those quoted by Boothroyd et al 7 (presented for frontal tube output only) but much higher than those reported by Rassow et al 32 for data acquired from 1994 to 1996. For both diagnostic and interventional categories, recent era P KA figures were compatible with the results of studies led by Martinez et al, 33 Dragusin et al 21 Two well-reported investigations by Verghese et al 16 (3365 procedures) and Glatz et al 31 (2265 procedures) have been published in which stratification of P KA by age or mass for individual procedure types was sufficient to allow meaningful comparisons. Given the modern equipment and the introduction of entirely sensible radiation protection measures such as reduced frame rates and antiscatter grid removal where appropriate, one would expect doses to be comparable to those of the present study over the same period; instead, they are higher by a factor of typically between two and ten, where matched for patient size and procedure type, both for P KA A recent study by Kobayashi and colleagues 18 was particularly ambitious, acquiring data from 16 centres giving a sample of 8267 procedures.…”
Section: Comparison With Previous Researchsupporting
confidence: 81%
See 1 more Smart Citation
“…The doses from the 1994 to 2000 era at Hospital 1 were compatible with those quoted by Boothroyd et al 7 (presented for frontal tube output only) but much higher than those reported by Rassow et al 32 for data acquired from 1994 to 1996. For both diagnostic and interventional categories, recent era P KA figures were compatible with the results of studies led by Martinez et al, 33 Dragusin et al 21 Two well-reported investigations by Verghese et al 16 (3365 procedures) and Glatz et al 31 (2265 procedures) have been published in which stratification of P KA by age or mass for individual procedure types was sufficient to allow meaningful comparisons. Given the modern equipment and the introduction of entirely sensible radiation protection measures such as reduced frame rates and antiscatter grid removal where appropriate, one would expect doses to be comparable to those of the present study over the same period; instead, they are higher by a factor of typically between two and ten, where matched for patient size and procedure type, both for P KA A recent study by Kobayashi and colleagues 18 was particularly ambitious, acquiring data from 16 centres giving a sample of 8267 procedures.…”
Section: Comparison With Previous Researchsupporting
confidence: 81%
“…The potential for relatively high radiation doses raises concerns of the long-term risk of developing cancer. [1][2][3] The radiation doses and associated risks from cardiac catheterizations in children and young people have recently received considerable attention, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] although relatively fewer data on doses in the UK have been published. 7,17,22,23 Most previous assessments have been based on kerma area product (P KA , also known as dose-area product), defined as collision air kerma integrated over beam area.…”
mentioning
confidence: 99%
“…For therapeutic procedures, these third quartile values were 1.0 Gy cm 2 (aortic angioplasty), 2.6 Gy cm 2 (pulmonary angioplasty), 5.6 Gy cm 2 (pulmonary angioplasty with stent), 1.7 Gy cm 2 (atrial septal defect closure), 2.3 Gy cm 2 (aortic valvuloplasty), 0.9 Gy cm 2 (pulmonary valvuloplasty), 1.2 Gy cm 2 (patent ductus arteriosus closure with coil), 1.9 Gy cm 2 (patent ductus arteriosus closure with device), and 4.4 Gy cm 2 (others). In their study, Dragusin et al 26 reported FT and DAP third quartile values from 11.0 to 18.0 min and from 4.1 to 16.5 Gy cm 2 , respectively, for diagnostic procedures and from 24. On the other hand, there are a higher number of studies detailing dose values grouped by age during pediatric cardiology procedures.…”
Section: Discussionmentioning
confidence: 89%
“…The 25 th , 50 th and 75 th percentile per each age group for diagnostic procedure is presented in Figure 4 and for therapeutic procedures is presented in Figure 5. (Dragusin et al, 2008a) Other study reported DAP values as 75th percentile of 6.2, 6.1, 9, 10, 15, 20, 27 and 36 Gycm² for 2114 patients divided in eight age groups from newborns to 21 y (Rassow et al,2000). This study included diagnostic, therapeutic and myocardial biopsy procedures.…”
Section: Patient Radiation Doses Radiation Doses During Pediatric Carmentioning
confidence: 98%
“…The main therapeutic procedures are balloon dilatation of the pulmonary valve, balloon dilatation of peripheral pulmonary stenosis, balloon dilatation for coarctation of the aorta, stent implantation, occlusion of patent ductus anteriosus, closure of atrial septal defect and closure of ventricular septal defect. We will discuss the results of a study regarding pediatric radiation doses performed in a catheterization laboratory equipped with a biplane FD system (Dragusin et al, 2008a). In this study, the population was divided in six age groups (0-30 days, 1-12 months, 1-3 years, 3-5 years, 5-10 years and 10-15 years).…”
Section: Patient Radiation Doses Radiation Doses During Pediatric Carmentioning
confidence: 99%